A portrait of the artist as a young teacher: James Joyce's walking-talking classroom. Issue 1 (April 2023) - Keohane, Kieran
This paper traces a deep affinity between teaching and learning, talking and walking. This affinity runs as a red thread from the Greeks walking to Delphi; to WalterBenjamin's (1992a) flâneur, the urban stroller in Paris and Berlin; to JaneJacobs' (1961) celebration of New York's 'sidewalk ballet'; toSimmel's (1971) discussion of the metropolis, mental life, and modernity's zeitgeist; to the Chicago and Birmingham schools' ethnographies of street scenes and subcultures byPark and Burgess (1925) andHebdige (1979) ; to Maggie O'Neill's (2018 ) O'Neill and Roberts (2019) use of 'walking methods' as a way into the fragile, precarious, liminal worlds of migrants, refugees, and sex-workers. O'Neill's renaissance of a deep tradition of walking-talking sociological methods resonates very well also with James Joyce's artistic, moral, political, and pedagogical method, whereby the author and his protagonists, (who are mostly people who have been crushed down and pushed to the margins by overwhelming global historical forces) and his readers (a literate, middle-class, cosmopolitan, general public) participate in and co-create a transformative walking-talking classroom convened and conducted through city streets, as exemplified in A Portrait of the Artist as a Young Man .